Aortic Arch Reconstruction in Neonates with Biventricular Morphology: Increased Risk for Development of Recoarctation by Use of Autologous Pericardium - Bechtold, Caroline; Purbojo, Ariawan; Schwitulla, Judith; Glöckler, Martin; Toka, Okan; Dittrich, Sven; Cesnjevar, Robert Anton; Rüffer, André (The Thoracic and Cardiovascular Surgeon, 2015)
Background The aim of this study was to analyze risk factors promoting development of recoarctation (Re-CoA) in neonates who survived aortic arch repair from an anterior approach.Methods Fifty consecutive neonates with biventricular morphology and ductal-dependent lower body perfusion who were discharged home following aortic arch repair with cardiopulmonary bypass between 2000 and 2012 were retrospectively reviewed. Arch anatomy was either interruption (n = 10) or hypoplasia with coarctation (n = 40). Aortic arch reconstruction was performed by using patch material (bovine pericardium, n = 30, homograft, n = 10, or glutaraldehyde-treated autologous pericardium, n = 7), and three patients underwent direct end-to-side anastomosis. Antegrade cerebral and continuous myocardial perfusion was performed in 39 and 21 patients, respectively. Kaplan–Meier freedom from Re-CoA was calculated. Morphologic and perioperative data indicating increased risk of Re-CoA by univariate analysis were included in multivariate Cox regression analysis.Results Mean follow-up was 5.3 ± 4.1 years. Re-CoA occurred in 13 patients and was treated successfully by balloon dilatation (n = 6) or surgery (n = 7). Freedom from Re-CoA after 1 and 5 years was 83 ± 5 and 79 ± 6%, respectively. Two patients died early after surgical repair of Re-CoA. The use of autologous pericardium for aortic arch augmentation was the only independent risk factor for development of Re-CoA (hazard ratio: 4.3 [95% confidence interval: 1.2–16.1]; p = 0.028).Conclusion Re-CoA following neonatal aortic arch surgery can be treated by balloon dilatation or surgery, if adequate. In this study, the risk for development of Re-CoA was independently increased by the use of autologous pericardium during initial arch repair.
Keywords: aorta/aortic; cardiac; congenital heart disease; pediatric